LEARNING INTEREST, ACHIEVEMENT MOTIVATION, LEARNING STYLE, AND SELF-RELIANCE OF LEARNING EFFECT ON STUDENT ACHIEVEMENT AT SMP BATIK SURAKARTA - Rahmawati, Rahmawati; Titisari, Kartika Hendra; Pawenang, Supawi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Learning achievement is one of the goals to improve the quality of learning in education. The success of a student in learning can be seen from his learning achievement, if learning is high then achievement will be high, otherwise if achievement is low then achievement will also be low. The purpose of this study was to determine the effect of interest, achievement motivation, learning style, and independent learning on student achievement at SMP Batik Surakarta. The population of this study were all students of the Surakarta Batik Junior High School at the VIII grade level for the 2020/2021 academic year, totaling 243 students. The sampling technique used simple random sampling and obtained a sample of 102 respondents. The method of collecting data is through a questionnaire of learning interest, achievement motivation, learning style and learning independence, while learning achievement is obtained from the archives of student scores. The instrument test uses validity and reliability tests. The data analysis technique used multiple linear regression hypothesis testing, t test, F test and R2 test. The results showed that interest in learning, learning motivation, learning style, learning independence had an effect on student achievement at SMP Batik Surakarta. The result of the determination coefficient test (R2) is 0.850 or 85%, meaning that together there is an influence between the independent variables, namely Learning Interest (X1), Achievement Motivation (X2), Learning Style (X3) and Learning Independence (X4) on Achievement Students (Y) at SMP Batik Surakarta are 85%, while 15% are influenced by other factors, which are not examined, such as family environment, social environment and others.